The commodification of mobile phone surveillance: An analysis of the consumer spyware industry. (March 2020) - Harkin, Diarmaid; Molnar, Adam; Vowles, Erica
This article examines the attempts of 'spyware' developers to commodify and market their products to a general audience. While consumers of 'spyware' have often been government and law enforcement (Citizen Lab, 2015), there is an increasing attempt to market, sell, and commodify 'spyware' for use by wider audiences. 'Spyware' is sold as a security product commonly aimed at businesses, parents, and intimate partners. Pursuant to calls for a "sociology of security consumption" (Goold et al., 2010: 3), this article analyzes how nine prominent spyware vendors attribute meaning to their products. Spyware vendors face particularly fraught marketing challenges as the general deployment of spyware: a) is often utilized in forms of intimate partner abuse; b) is "morally troubling" from the perspective of being corrosive to many forms of social relations (Loader et al., 2014: 469); and c) has limited contexts where it could be deployed without violating surveillance laws. More specifically, this article compares the social meaning that vendors attempt to give to spyware and contrasts this with the powers of surveillance provided by the product, the marketing messages that appear to support non-consensual use, and the lack of guidance for non-consenting spyware targets to have recourse with the vendors.